RETRACTED: Upregulation of C Terminus of Hsc70-Interacting Protein Attenuates Apoptosis and Procoagulant Activity and Facilitates Brain Repair After Traumatic Brain Injury - Chen, Hao; Jing, Yao; Xu, Zhiming; Yang, Dianxu; Ju, Shiming; Guo, Yan; Tian, Hengli; Xue, Lixia (Frontiers in Neuroscience, 2020)
Traumatic brain injury (TBI) could highly induce coagulopathy through breaking the dynamic balance between coagulation and fibrinolysis systems, which may be a major contributor to the progressive secondary injury cascade that occurs following TBI. Phosphatase and tensin homolog deleted on chromosome ten (PTEN) inhibition is reported to exert neuroprotective in TBI, making it a potential regulatory target involved in TBI-induced coagulation disorder. PTEN level is controlled in a major way by E3 ligase-mediated degradation through the ubiquitin-proteasome system. The C Terminus of Hsc70-interacting Protein (CHIP) has been shown to regulate proteasomal degradation and ubiquitination level of PTEN. In the present study, CHIP was overexpressed and knocked down in mouse brain microvascular endothelial cells (bEnd.3) and tissues during the early phase of TBI. In vitro cell proliferation, cell apoptosis, migration capacity, and invasion capacity were determined. The changes of procoagulant and apoptosis molecules after TBI were also detected as well as the micrangium density and blood brain barrier (BBB) permeability after in vivo TBI. In vitro results demonstrated that CHIP overexpression facilitated bEnd.3 cells proliferation, migration and invasion, downregulated cell apoptosis and the expressions of procoagulant molecules through promoting PTEN ubiquitination in an simulated TBI model with stretch-induced injury treatment. In vivo experiments also demonstrated that CHIP overexpression suppressed post-TBI apoptosis and procoagulant proteins expressions, as well as increased microvessel density, reduced hemorrhagic injury and BBB permeability. These finding suggested that the upregulation of CHIP may attenuate apoptosis and procoagulant activity, facilitate brain repair and thus exerts neuroprotective effects in TBI.